Pacific paradisen [videorecording] - Howes, Oliver; Numfress, Paul. ([S.l.] Film Australia, 1988)
Summary: Shows the Kiribatis, Tahitians, and the Bikini Atoll natives way of life.
Contents: Part I. Kiribati -- Part II. Tahiti -- Part III. The Marshall Island
Credits: Editor, Anton Horak.
Keywords: Oceanians